FSO/CV-QKD/QBaudSK system based on 2PolSKBPSK scheme considering dynamical atmospheric conditions - López-Leyva, Josué Aarón (My University, 2019)
EXPERIMENTAL SET-UP Alice uses a laser (λ=1550.1 nm) to generates Coherent States (CS) with diffused phase / Phase Modulator (PM) modifies the optical phase based on a BPSK scheme and a PolM modifies the SOP related to the 2PolSK modulation scheme / The PM and PolM are drives by digital TRNG / After, Alice and Bob use an optical signal of 100nW and 2mW (necessary for reach the Standard Quantum Limit, SQL) / At the Bob’s side, a free space π/2 optical hybrid uses the SOPs of the two optical signals for the simultaneous detection of the conjugate variables of the Weak Coherent State (WCS) due to that performance depends of the degree of polarization (DOP) / Thus, the output electrical current of Balanced Homodyne Detection (BHD) represents the information of the quadrature components of the quantum state transmitted / It is important to mention that the WCS is transmitted through a unidirectional free space channel and the dynamical atmospheric conditions are emulated by an atmosphere turbulence box.
Keywords: e quantum state transmitted; Coherent states; Campus Mexicali